THE EFFECT OF THE HIWAR METHOD BY USING A POCKET INDONESIAN-ARABIC DICTIONARY IN IMPROVING SPEAKING SKILLS (EXPERIMENTAL STUDY IN CLASS 2 MTSS NURUL ISLAM): تأثير طريقة الحوار باستخدام قاموس الجيب الإندونيسي- العربي لترقية مهارة الكلام في الفصل الثاني بالمعهد نور الإسلام - Amna, Zuriah (Institut Agama Islam Negeri Lhokseumawe, 2023)
This article is entitled The Effect of the Hiwar Method by Using a Pocket Indonesian-Arabic Dictionary in Improving Speaking Skills (an Experimental Study in Class 2 MTsS Nurul Islam). Researchers chose this title because they saw problems found in the field, including students were rarely expressing their thoughts using the Arabic, students also having difficulty translating words or sentences in Arabic books or texts, and rarely using dictionaries both during the learning process and outside the learning class. Thus, this research aims to determine the effectiveness and influence of the hiwar method by using a pocket Indonesian-Arabic dictionary in improving their speaking skills. Meanwhile, in writing this article, the researcher used an experimental approach by employing data collection techniques in the form of tests. The population in this study were all 2nd grade students at MTsS Nurul Islam, consisting of 66 students. Meanwhile, the sample was students of class 2(b) as the experimental group, and students of class 2(a) as the control group with a total of 22 students in the experimental group and 19 students in the control group. After the researcher carried out the data analysis using the t-test with ∝ = 0.05 and dk = 39, the result showed is Tcount>Ttable, namely 5.769>1.685, this shows that there is an influence of the hiwar method using an Indonesian-Arabic pocket dictionary on the speaking skills of grade 2 students at MTsS Nurul Islam.